DEVELOPMENT OF FILLER FROM LOKOJA BENTONITE CLAY FOR APPLICATION IN THE PRODUCTION OF PLASTER OF PARIS (POP) - Uthman, Habibu; Danjuma, Dirisu Abraham (FUDMA JOURNAL OF SCIENCES, 2025)
This research aimed at enhancing the production of plaster of Paris (POP). Compressive strength, flexural strength, water absorption, density and setting time tests were carried out on these samples. The Bentonite clay collected from the Lokoja mining site were processed and characterized with the sample on the average having compressive strength of up to 0.000148 N/mm2, 0.000284 N/mm2 and 0.000385 N/mm2, flexural strength of 0.7 N/mm2, water absorption of 0.46–0.60%, 1.00–1.43% and 1.43–2.08% setting time of 15 minutes and 58 seconds. The compressive strength test results reveal a positive progression in strength over the curing period, with developed plaster of Paris (DPOP) consistently outperformed commercial plaster of Paris (CPOP). The flexural test demonstrates DPOP superior resistance to bending stresses, providing insights into its potential applications in construction industries. The water absorption test, conducted at varying calcination temperatures and times, elucidates the material’s porosity/absorbency characteristics, offering valuable information for applications where resistance to moisture is critical. The setting time test results provide crucial data on the workability and usability of the plaster, indicating that DPOP exhibits a slightly longer final setting time compared to CPOP. Properties obtained from the characterized DPOP revealed that sample collected from the Lokoja mining site and well processed can replace CPOP in the market because of their outstanding properties which exceeded CPOP. This approach utilized in the development of POP from locally sourced bentonite clay emphasizes its potential for various applications.